2003
DOI: 10.1590/s1516-44462003000400013
|View full text |Cite
|
Sign up to set email alerts
|

"Quality of life": a brand new concept for research and practice in psychiatry

Abstract: Since the '70s, the assessment of quality of life (QOL) has grown from a 'small cottage' industry to a formal discipline within a coherent theoretical framework, accepted methods, and manifold applications. In recent years, QOL has become increasingly popular as a useful variable tailored to assess the overall impact of diseases and medical treatments from the patient's point of view. In this updating paper, we describe the most frequently used instruments, and discuss the conceptual and practical issues conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
34

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(81 citation statements)
references
References 11 publications
4
43
0
34
Order By: Relevance
“…This study demonstrated that the presence of any type of emotional distress was associated with lower quality of life scores, as previously reported in the literature 28,29,30 . A study conducted in England found lower scores for those suffering from common or severe mental disorder compared to those considered healthy; in turn, those suffering from severe mental disorder scored still lower than those from the other two analysis groups (healthy and suffering from common mental disorder) 31 .…”
Section: Discussionsupporting
confidence: 89%
“…This study demonstrated that the presence of any type of emotional distress was associated with lower quality of life scores, as previously reported in the literature 28,29,30 . A study conducted in England found lower scores for those suffering from common or severe mental disorder compared to those considered healthy; in turn, those suffering from severe mental disorder scored still lower than those from the other two analysis groups (healthy and suffering from common mental disorder) 31 .…”
Section: Discussionsupporting
confidence: 89%
“…Além disso, pode ser utilizado tanto para populações saudáveis como para populações acometidas por agravos e doenças crônicas 20 .…”
Section: Métodounclassified
“…As medidas de qualidade de vida em Psiquiatria são potencialmente úteis tanto na prática clínica como em pesquisas, pois podem demonstrar o impacto das doenças mentais e possíveis benefícios dos tratamentos 12 .…”
Section: Resultsunclassified
“…A avaliação da qualidade de vida nos últimos anos vem sendo útil para determinar o impacto das doenças e dos tratamentos a partir da perspectiva dos pacientes 12 . O uso dessas medidas pode beneficiar os pacientes, pois seus problemas são identificados e as decisões do tratamento podem ter como base suas preferências e habilidades.…”
Section: Resultsunclassified